Review on injuries in the Olympic sport taekwondo in training and competition, prevention recommendations - Athanasiou, A.; New, K. (Medicina dello Sport, 2021)
INTRODUCTION: To identify, investigate and analyze taekwondo injuries during training and competition and create a comprehensive injury prevention plan. EVIDENCE ACQUISITION: The USW online library and reputable medical websites (PubMed, Google Scholar, Cochrane Library) to access the current literature regarding taekwondo injuries, from December 2019 until March 2020. Included studies were accepted if published between 2004 and 2019 and contained details regarding incidence, gender, location of the injury, type, mechanism and severity. Injuries were classified into acute and chronic with special consideration to concussions and chronic traumatic encephalopathy. EVIDENCE SYNTHESIS: Fifteen studies were included in the study, either retrospective studies or literature reviews. All studies regarding acute injuries, concluded that the most common injured body part is the lower limb, and the severity of the injuries is usually minor. Both genders are affected equally, and the types of most prevalent injuries are contusions, lacerations, strains and sprains. Overall, there are 79.3 injuries observed every 1000 A-Es (athletes` exposures). Receiving or delivering a kick was identified as the most typical mechanism of injury. Concussions are occurring more frequently among male athletes and in taekwondo the number of concussions is 4 times higher than in American Football. Recent implementation of electronic gear has shown a decrease in injuries during competition. Catastrophic injuries are very rare in taekwondo and current literature has no reference of catastrophic injuries during fighting competition. With regards to chronic injuries, the lower extremity and lower back are the most affected body parts and female athletes seem to have higher numbers of chronic injuries reported in the studies. CONCLUSIONS: Minor acute and chronic injuries are common in taekwondo and concussion rate is amongst the highest in sports. Various preventive measures exist and should be implemented together with amendments in sport rules during competition. International and National directories should be formed to report, review and prevent injuries in taekwondo.